Fracturing evolution analysis of Beishan granite under true triaxial compression based on acoustic emission and strain energy. (May 2019) - Zhang, Yan; Feng, Xia-Ting; Yang, Chengxiang; Zhang, Xiwei; Sharifzadeh, Mostafa; Wang, Zhaofeng
Abstract: The study of rock fracturing is a fundamental research topic in rock mechanics and engineering. In this paper, based on complete stress–strain curves obtained under TTC and the corresponding AE and strain energy results, the mechanical properties and fracturing process of Beishan granite are studied. A representative test result ( σ 2  = 75 MPa, σ 3  = 20 MPa) is selected to analyse and illustrate the three-dimensional fracturing process of the Beishan granite. The results show that the variations in the characteristics of the brittle fracture behaviour, AE and strain energy of Beishan granite change with σ 2 or σ 3 following certain relationships, and the mechanisms driving these various relationships are very different. The AE and strain energy characteristics of Beishan granite are also quite different among the five fracturing evolution stages. The variations in the increments of AE count, AE event and total elastic strain energy per unit time ( ΔS c / Δt, ΔS e / Δt and ΔU e / Δt ) are studied at different times and under different stresses during rock failure. The rock fracturing evolution can be illustrated through the variation in these parameters, providing deep insight. This research provides a perspective for studying deep underground fracture-forming processes, such as earthquakes, tunnel sudden failure, spalling, splitting and rockburst.